Early growth response and nutrients quality of fig (Ficus carica l.) planted on bris soil effected by chicken manure amendments - Azmi, Fatin Munirah; Tajudin, Nur Shuhada; Shahari, Rozilawati; Che Amri, Che Nurul Aini (Zibeline International Publishers, 2020)
Allah S.W.T swears by the fig tree (Sura’ 95, al-Tin) in the holy Quran, for its values and practices. Recently, the fig tree (Ficus carica L.) has been introduced in Malaysia’s tropical weather as it grows well with maximum activity. Its root favors a well-drained type of soil, and since BRIS (Beach Ridges Interspersed with Swales) are dominated by sandy texture with proper water percolation, it has a high potential for fig planting. However, BRIS is known to have low nutrient holding capacity but can be improved with organic amendments. This study was carried out to determine the effects of various rates of chicken manure as amendments in improving the BRIS soil health for the growth of fig trees. The BRIS soil was amended with different rates of 10% (T2), 20% (T3), 30% (T4), and 50% (T5) of chicken manure and 0% (T1) as control. Three months old saplings were propagated through hardwood cuttings of variety BTM6 with five replications in each treatment. The growth response and nutrients quality of the fig trees were observed biweekly for three months after the transplant, and the nutrient contents of amended and non-amended showed significant differences at p<0.05. The survivability of the trees was 100%, and a significant difference was found between the treatments. BRIS soil with 40% chicken manure amendments (T4) showed superlative growth response with the highest number of branches, leaves, and fruits, thus provide higher yield production as compared to other treatments. From this study, BRIS soil that is known to be problematic can be improved with correct rates of organic amendments and can be used for fig cultivation.